2014
DOI: 10.1155/2014/790350
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Panton-Valentine Leukocidin (PVL) Genes in Nosocomial-AcquiredStaphylococcus aureusIsolated from Tertiary Care Hospitals in Nepal

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) carrying the important virulence determinant, Panton-Valentine leukocidin (PVL), is an emerging infectious pathogen associated with skin and soft tissue infections as well as life-threatening invasive diseases. In carrying out the first PVL prevalence study in Nepal, we screened 73 nosocomial isolates of S. aureus from 2 tertiary care Nepali hospitals and obtained an overall PVL-positivity rate of 35.6% among the hospital isolates: 26.1% of MRSA and 51.9% of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
4
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 28 publications
3
28
4
1
Order By: Relevance
“…It seems that PVL carrying phages were integrated into pre-existing endemic MRSA strains; therefore, a previously accepted hypothesis about markers of CA-MRSA strains could be speculated. Our findings and some previous studies suggest that the PVL gene could not be an appropriate marker for CA-MRSA (9,10,27,(37)(38)(39). Altogether, these findings are alarming with respect to the genetic background of these HA-MRSA strains (ST239/SCCmec III), since it is possible that these highly virulent strains spread to other hospitals in various geographical regions.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…It seems that PVL carrying phages were integrated into pre-existing endemic MRSA strains; therefore, a previously accepted hypothesis about markers of CA-MRSA strains could be speculated. Our findings and some previous studies suggest that the PVL gene could not be an appropriate marker for CA-MRSA (9,10,27,(37)(38)(39). Altogether, these findings are alarming with respect to the genetic background of these HA-MRSA strains (ST239/SCCmec III), since it is possible that these highly virulent strains spread to other hospitals in various geographical regions.…”
Section: Discussioncontrasting
confidence: 53%
“…Phage harbored Panton-Valentine Leukocidin (PVL) is one of the most important toxins (8). This is a twocomponent toxin encoded by phage that can be inserted into the S. aureus genome (9). This toxin was introduced as one of the CA-MRSA markers, especially in skin and soft tissue infections (10).…”
Section: Introductionmentioning
confidence: 99%
“…Type IV is classified to IVa, IVb, IVc and IVd alleles [9]. Data revealed that PantonValentine Leukocidin (PVL) is the most important virulence factor detected in the MRSA strains isolated from the cases of foodborne and clinical infections [10]. Inappropriately, major principles of food hygiene have not been addressed in most Iranian restaurants.…”
Section: Staphylococcalmentioning
confidence: 99%
“…The luk-PV gene was found in 5% of blood and 3% of pharynx samples. Overall, the prevalence of the luk-PV gene has been estimated to be 2-35% among MRSA isolates in various types of nosocomial infections [34,35] Although the association between luk-PV gene and CA-MRSA strains is a subject of debate, to date, PVL has emerged as a significant virulence factor of CA-MRSA isolates making it a putative marker of these strains [37]. In a study conducted by D'Souza et al in Mumbai between 2006 and 2009, it was found that none of the HA-MRSA isolates carried the luk-PV gene [38].…”
Section: Discussionmentioning
confidence: 99%